O uso do software régua e compasso na aprendizagem do conceito de cálculo de áreas de figuras planas no ensino fundamental - Abreu, Silvio Luis Amâncio de (2014)
This research aims to use the Ruler and Compass software in performing activities that seek to build the concept of calculation of areas of plane figures at the elementary school level and to promote interaction between teacher-student and studentstudent. Also seeks to analyze the methodological ways to present concepts to calculate areas of plane figures through the use of Ruler and Compass software, worrying associate it in the school curriculum.